Internal Quality Assurance Practices and Andragogy in Higher Education Institutions: Implications for PhD Training in Uganda - Netalisile Malunda, Paul; Namubiru Ssentamu, Proscovia; Atwebembeire, Juliet (African Journal of Governance and Development, 2021)
Higher Institutions of Learning will significantly contribute to the transformation of society and economic development of any country when their training approaches focus on developing graduates who generate new knowledge and skills meant to address multiple social, economic and environmental issues. Using a critical narrative literature review, this article examines the contribution of internal quality assurance practices to andragogy in higher education institutions (HEIs) in Uganda. It specifically focuses on staff development and student evaluations as key internal quality assurance practices that explain the application of andragogy in the training of Ph.D. students. The article discusses the current state of training of doctoral students in Uganda and recommends the following strategies for HEIs so as to promote the quality of delivery for doctoral students: i) pursue vigorous staff development programmes to equip lecturers with the necessary andragogical skills to facilitate students’ development of necessary work-based and other competences needed to address Uganda’s social, economic and political issues, ii) systematically and routinely monitor and evaluate the teaching and learning process to inform decision making on quality assurance and teaching practices, and iii) utilise students’ evaluations of the Ph.D. delivery approaches to establish the relevance and improvement of the curriculum.
Keywords: Internal Quality Assurance; Andragogy; Higher Education Institutions